ANALYSIS OF COST AND RETURNS IN RICE PRODUCTION BY USAID-MARKETS II PROJECT PARTICIPANTS AND NON-PARTICIPANTS IN EBONYI STATE, NIGERIA - Ogechi Cordelia Nwahia (Socio-Economics/Agribusiness Department, 2021)
This research work focused on analysis of cost and returns in rice production by USAID-MARKETS II project participants and non-participants in Ebonyi state, Nigeria. Multi-stage sampling procedure was employed to select 239 participants, and 252 non- participants for the study. Data were collected from primary source, and analyzed using Z statistic, Net Farm Income (NFI) and Returns Per Naira Invested (RNI). The result reveals that the Net Farm Income (NFI) obtained by USAID-MARKETS II project participants, and non-participants were N493, 067.55/ha, and N353, 408. 12/ha respectively while the return on investment obtained by them were N3.28k, and N3.05k respectively. There was a significant difference between the profits obtained by them. Therefore, this study recommended that the teaming unemployed Nigerian youth should be encourage by the government, and international agencies through provision of grant/loan to take up rice farming as a business.